INTELLECTUAL RESOURCES AS A CATALYST FOR REGIONAL BUSINESS - Svetlana A. Gusar (Статистика и экономика)
In the article the author examines the conditions of development and the process of intellectualization of regional business. The conclusion says about the necessity of the intellectual potential of regional business formation due to the fact that the intellectualization is a driver of economic growth and the basis of regional competitiveness, but perhaps it is only in the interaction between business and government, the creation of viable and effective vertical and horizontal communication, as well as a network of institutions that supports and intellectualization development of entrepreneurship and providing infrastructural support.